Análise do impacto da inserção de veículos elétricos na rede elétrica da UFPB - Farias Neto, João Soares (2022)
The energy currently consumed by the Federal University of Paraíba (UFPB) exceeds, in some periods, the demand limits contracted by the university, which can result in tariff fines and consequently an increase in expenses. This increase in costs could be avoided by managing energy demand through an intelligent electrical grid by adding Electric Vehicles (EVS) that compensate for excess demand by injecting power into the grid when necessary. In this context, this work addresses a case study on the possibility of integrating an intelligent electrical grid with Vehicle to Grid (V2G) as a demand management mechanism, considering its technical and economic feasibility, as well as an impact analysis methodology. of the insertion of EVs in electrical networks available for use by other authors. For that, it was considered the survey of the percentage of the increase of electric vehicles in Paraíba, the study of the scenarios of opportunity for charging vehicles at the university, the possibility of supplying energy from the vehicle to the UFPB network and the impact on the electric network. of the university without and with load management. The results show that EVs operating with the V2G network can reduce up to 77.66% of fines without consumer benefits from load management, and this financial savings could be used as an incentive for EV owners to allow the exchange of energy with the university's network during the period of stay at UFPB.